Pengaruh Infrastruktur Ekonomi dan Infrastruktur Sosial Terhadap Produk Domestik Regional Bruto di Kawasan Timur Indonesia Tahun 2011-2020 (Studi Kasus 16 Provinsi di Kawasan Timur Indonesia) - Jussara Riska Amelya; Jean Elikal Marna (Jurnal Salingka Nagari, 2023)
This study aims to determine the effect of Economic Infrastructure as measured by the length of roads in each province in eastern Indonesia, Economic Infrastructure as measured by electricity and Social Infrastructure, namely education as measured by the number of schools on GDRP in 16 eastern provinces of Indonesia within 10 years. year, namely from 2011-2020. This study used a secondary method and the data were obtained through BPS publications. The analysis used in this study is panel data regression analysis using the Random Effects Model Approach. The results of this study indicate that Economic Infrastructure (Roads) has a positive but not significant effect, Economic Infrastructure (Electricity) has a positive and significant effect, and Social Infrastructure (Education) has a positive but not significant effect on GRDP in eastern Indonesia in 2011-2020